Experimental and numerical studies on the cyclic performance of structural frames equipped with bar dampers - Ghaedi, Khaled; Javanmardi, Ahad; Ibrahim, Zainah; Gordan, Meisam; S. M. Rashid, Raizal; Khatibi, Hamed; Vaghei, Ramin (Elsevier, 2023)
This study presents the effectiveness of a new metallic damper called bar damper (BD) in improving the cyclic performance of a semi-rigid frame. The BD consists of solid bars sandwiched between a top and a bottom plate. These solid bars dissipate the applied external energy through plastic deformations. To evaluate the BD effectiveness, a preliminary pushover analysis was performed on a semi-rigid frame equipped with BD devices and compared to bare rigid and semi-rigid frames to get a perception of the BD effect on stress distributions of the frames. Further, a series of quasi-static cyclic displacement tests were performed experimentally on semi-rigid frames with and without the BD devices. The maximum applied displacement load on the frames was designed based on the actuator head movement limits. Further, three-dimensional finite element (FE) models were developed and validated with the experimental results and they were compared where the results showed an acceptable agreement. It was observed from the results that the BD devices noticeably improved the performance of the frame in terms of strength, effective stiffness, damping ratio, and energy dissipation capacity.